142k views
3 votes
HELPPPPPPPPPPPPPPPPPPPPPPPPPPPPPP

HELPPPPPPPPPPPPPPPPPPPPPPPPPPPPPP-example-1
User Peymankh
by
6.2k points

2 Answers

4 votes
6))
the answer is 6
(corrected)

User JarrettV
by
6.5k points
1 vote
What you should keep in mind in this case is that you have an absolute value function.
You must replace x = -10 in the equation.
We have then:
b (x) = lx + 4l
b (-10) = l-10 + 4l
b (-10) = l-6l
b (-10) = 6
Answer:
The function evaluated at x = -10 is:
b (-10) = 6
User Shameca
by
6.0k points